Mood Changes and Physical Activity Patterns in Adolescents - Ferdy Febrian; Kuston Sultoni; Mohammad Zakky; Jajat (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to analyze the relationship between physical activity patterns and mood changes in adolescents using an objective measurement approach. This cross-sectional study involved 50 adolescent participants. Physical activity was measured using the ActiGraph GT3X accelerometer, while mood changes were assessed using the Brunel Mood Scale (BRUMS). Data were analyzed using Spearman’s correlation test with a significance level of p < 0.05. Findings indicate that participants spent most of their time engaged in sedentary behavior (M = 1194.42 minutes/day, SD = 42.543), while moderate-to-vigorous physical activity (MVPA) levels were relatively low (M = 47.06 minutes/day, SD = 17.873). Negative mood states were more dominant than positive ones, with the highest scores recorded for tension (M = 65.22, SD = 12.255) and anger (M = 63.06, SD = 10.033). Correlation analysis revealed no significant relationship between total MVPA and mood (r = -0.021, p = 0.886). However, sedentary behavior showed a significant negative correlation with moderate physical activity (r = -0.626, p < 0.01) and total MVPA (r = -0.635, p < 0.01), indicating that higher sedentary time was associated with lower levels of physical activity in adolescents. This study found no significant relationship between physical activity and mood changes in adolescents. The low levels of MVPA and high sedentary behavior may contribute to the dominance of negative mood states. Further longitudinal studies are needed to explore other factors that may influence adolescent emotional well-being.